Becoming a physician : a practical and creative guide to planning a career in medicine - Danek, Jennifer; Danek, Marita, 1942- (New York : Wiley, 1997)
A guide to becoming a physician, reviewing the application process, providing information on the MCAT entrance exam, offering advice on selecting a medical school, and considering specialization.
Includes bibliographical references (p. 210-212) and index.
Adult
Keywords: Medical colleges -- Admission; Medicine -- Vocational guidance; Medical colleges -- Entrance requirements; Medicine -- Vocational guidance